URGENSI FIQIH LINGKUNGAN DALAM PERKEMBANGAN FIQIH KONTEMPORER SEBAGAI INSTRUMEN PENDUKUNG HUKUM LINGKUNGAN - Mu'adil Faizin (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
The environmental problem becomes most problems. Getting many theories of the cause of enviromental crisis, finally on one theory, it is caused by spiritual crisis. It is enough sadly seeing Indonesia with the most islamic societies that can’t drop the enviromental crisis. Actually, Indonesia has had the keeping environmental instrument, but it is still weak. Consequently, the researcher discusses Urgency Of Islamic Environment Law In Development Of Islamic Modern Law As The Supportive Environmental Law Instrument. The research is library research which uses the analysis method to content analysis. The research discovers islamic environment law getting the ushul fiqih foundation that is the maslahah concept and the saddu zari’ah concept, and then a fiqih theory ((الضَّرَرُ يُزَالُ which means worse that must be deleted. The imbalance of understanding societies of the environment becomes the most of problems so that islamic environment law is urgent to develop that becomes Islamic modern law in the new knowledge and one of the supportive environmental law instruments, remembering that the religious norm gets similiar to the law norm.